Correcting the nomenclature of two Helix dejecta: Helicopsis arenosa (Krynicki, 1836) (Gastropoda: Hygromiidae) from Eastern Europe and Streptartemon dejectus (Moricand, 1836) (Gastropoda: Streptaxidae) from Brazil - Hausdorf, Bernhard (Zootaxa, 2013)
In the course of the preparation of a checklist and an atlas of the terrestrial molluscs of the Caucasus region it turned out that two species have been named Helix dejecta, one from the northern Black Sea region and one from Brazil, and need a nomenclatural clarification.